HUBUNGAN PERAN KEKUATAN KARAKTER DENGAN RESILIENSI PERAWAT DI RUMAH SAKIT - Paendong, Marsel; Buanasari, Andi; Mariana, Dina (JURNAL KEPERAWATAN, 2025)
Background: Work Stress due to a high workload on nurses is the impact of the low a nurse resilience behavior. The role of the character power from each nurse can be built and improved by a nurse resilience behavior, so that a nurse can be endured and able to face allthe challenges or work stress that they are facing. Objective : Of this research was aimed at knowing the correlation between the character strength and the nurse resilience at Gunung Maria Hospital of Tomohon. Methods: Was employed in this research was quantitative with cross sectional, the sample technique was non-probability sampling with total sampling. The data collection was questionnaire consisted of 154 respondents. The data were analyzed using the spearman rank correlations test. Results : There was a significant p value = 0.000 <= 0.05 with a correlation coefficient value = 0.297 which means the strength of the relationship between the role of character strength variables and nurse resilience is sufficient and has a positive value, which means that both variables are unidirectional so it can be interpreted that the higher the character strength role score. then the resilience score is also getting higher. Conclusion : There is a relationship between the role of character strength and the resilience of nurses at Gunung Maria Hospital. It is recommended to the nurses at Gunung Maria Hospital of Tomohon to try to improve their role of character strength in building resilience behavior so that they can endure and able to face all the challenges or works stress that they are facing.